Realistic Mathematics Education (RME) as an instruction design perspective for introducing the relationship between the derivative and integral via distance education - Kizito, Rita Ndagire (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.